Noragami : Stray god 12 - Adachi, Toka (Noragami, 2016)
Now that Yato has finally figured out what he wants out of life, he and Yukine are back in action, making the world a better place. Meanwhile, Hiyori is having troubles of her own. What can Yato do to help the one person he truly wants to make happy?